Consequences of amblyopia on education, occupation, and long term vision loss. Issue 9 (17th August 2004) - Chua, B; Mitchell, P
Abstract : Aims: To describe the effect of amblyopia on education, occupation, and 5 year incident vision loss. Methods: 3654 participants aged 49 years or older participated in the Blue Mountains Eye Study (BMES I, 1992–4) and 2335 (75·1% of survivors) were re-examined (BMES II, 1997–9). All participants underwent detailed eye examination. Amblyopia, defined as best corrected visual acuity of less than or equal to 6/9 and not attributable directly to any underlying structural abnormality of the eye or the visual pathway, was identified in 118 participants (3.2%) in BMES I, of whom 73 were re-examined in BMES II. Occupation and educational classifications used definitions of the Australian Bureau of Statistics. Results: The mean age of people with amblyopia seen at baseline was 67.0 years. Amblyopia did not affect lifetime occupational class (p = 0.5), but fewer people completed higher university degrees (p = 0.05). In people with amblyopia, there was an increased risk of 5 year incident visual impairment in the better seeing eye worse than 6/12, relative risk (RR) 2.7, 95% confidence interval (CI) 1.6 to 4.6. One of 11 (9.1%) people with amblyopia showed significant improvement in visual acuity in the poorer seeing eye after a two line (10 logMAR letter) vision loss in the better seeing eye. Conclusion: This study further documents the longitudinal history of amblyopia using population based data.